Does International Competition Enhance Capacity Utilisation? Evidence from Indonesia, Philippine and Vietnam - Pidani , Rita R; Mahmood, Amir (Asian Journal of Empirical Research, 2016)
This paper uses firm-level data of small and medium manufacturing firm in Indonesia, Philippine and Vietnam and studies the relationship between capacity utilisation and foreign market competition for the possibility of efficient firms self-selecting themselves instead of learning-by-exporting to enter the foreign markets. Estimating both linear and quadratic model on an unbalanced variance of exporting and non-exporting firms shows that the impact of foreign market competition on capacity utilisation is following a curvilinear relationship with a diminishing marginal point of as a constraint for further expansion. Capacity utilisation rate higher in non-exporting group is not only emphasizing a strong domestic market orientation of firms at large but also indicating the selection of learning-by-exporting entry mode by exporter SMEs in these countries. The paper further explores the impact of firm and industry physiognomies on a firm’s capacity utilisation and finds that the effects of wage productivity, competition, firm size, and legal structure are linearly positive and capacity dependent. The results throughout maintain the importance of capacities, competitiveness, and institutional performance as priorities to promote SMEs growth.